Three Multicenter, Randomized, Double‐Blind, Placebo‐Controlled Studies Evaluating the Efficacy and Safety of Ustekinumab in Axial Spondyloarthritis. Issue 2 (29th December 2018) - Deodhar, Atul; Gensler, Lianne S.; Sieper, Joachim; Clark, Michael; Calderon, Cesar; Wang, Yuhua; Zhou, Yiying; Leu, Jocelyn H.; Campbell, Kim; Sweet, Kristen; Harrison, Diane D.; Hsia, Elizabeth C.; et al.
Abstract : Objective: To evaluate the efficacy and safety of ustekinumab in 3 randomized, placebo‐controlled studies in patients with axial spondyloarthritis (SpA). Studies 1 and 2 included patients with radiographic axial SpA (anti–tumor necrosis factor [anti‐TNF]–naive patients and patients with inadequate response or intolerance to anti‐TNF, respectively); study 3 patients had nonradiographic axial SpA. Methods: In all 3 studies, patients were randomly assigned (1:1:1) to receive subcutaneous ustekinumab at 45 mg or 90 mg or placebo up to 24 weeks, after which placebo‐treated patients were rerandomized to receive ustekinumab at 45 mg or 90 mg. The primary end point in studies 1 and 2 was the proportion of patients who met the Assessment of SpondyloArthritis international Society criteria for 40% improvement in disease activity (achieved an ASAS40 response). The primary end point in study 3 was the proportion of patients who achieved an ASAS20 response. Other disease activity and safety measures were also evaluated. A week 24 analysis of study 1 was preplanned to determine continuation of studies 2 and 3. Results: For study 1, the primary and major secondary end points were not met, and the study was discontinued. As a result, studies 2 and 3 were prematurely discontinued before they were fully enrolled. For all 3 studies, neither ustekinumab dose group demonstrated clinically meaningful improvement over placebo on key efficacy end points. The proportion of patients experiencing adverse events in the ustekinumab groups was consistent with that in previous studies. Conclusion: In these 3 placebo‐controlled trials, efficacy of ustekinumab in the treatment of axial SpA was not demonstrated. The safety profile was consistent with that of studies in other indications.